The effect of temperature, static load, and electron irradiation on the deformation of linear polymeric films - Kupchishin, A.I.; Niyazov, M.N.; Taipova, B.G.; Khodarina, N.N.; Shakhanov, K.S.; Tronin, B.A. (Recent Contributions to Physics, 2018)
Experimental studies on the effect of temperature, static load and electron irradiation on the de-formation of polytetrafluoroethylene were carried out. Up to 35 °C the influence of load and tempera-ture leads to a sharp elongation of the samples, which is caused by the rectification of swirling com-plexes of macromolecules and rigidly connected chains. A catastrophic failure of weak circuits, includ-ing those associated with the presence of phase transitions occurs with increasing temperature to 45 °C. Curve (t) has a trend of a gradual recovery in the saturation at t > 40 °C, which is associated with rupture of the hard, more durable chains. The maximum deformation of 500 % is achieved at t = 85 °C and σ = 13 MPa. Dependences of the return deformation on time at static load and room tempera-ture are investigated. With increasing radiation dose, the return deformation decreases, and the strength limit of the polymer takes the value equal to 6 – 9 MPa. Electronic effects on literature the leads to a decrease in ductility and a significant decrease in recurrent strain that is associated with the destruction of the polymer. The curves described in the exponential model show satisfactory agree-ment of the experimental data with the calculation.
Keywords: temperature, deformation, strength, linear polymers, static load, irradiation, absorbed dose, mathematical model